Beneficial arthropods in the edible amaranth ecosystem during the wet season - Sri Nur Aminah; Tamrin Abdullah; Rezki Miranda; Dasmawati Dasmawati (Wallacea Plant Protection Journal, 2025)
The edible amaranth (Amaranthus tricolor L.) is an important vegetable growing around the world. The famous vegetable plant is known for two types: green and green-red amaranth. The purpose of the research is to study an abundance of beneficial arthropods in the edible amaranth ecosystem using pitfall trap. The study was conducted in the edible amaranth farmers plantation at Kanreapia Village, Gowa Regency, South Sulawesi in the wet season from August to December 2022. The pitfall trap was embedded into the ground at the same depth as the soil surface for 24 hours. The position of a pitfall trap in the center and every corner of the plot. The pitfall used five pieces for every plot (total 20 pitfall). The result showed important predator arthropods collected from pitfall traps were divided into two groups: spiders and insects. In this research, the beneficial arthropods are found in similar habitats in the edible amaranth. The highest percentage was Gryllidae such as Gryllus sp. (54.83%). The spiders group from Lycosidae, Lycosa pseudoannulata (25.80%) and from Oxyopidae, Oxyopus sp. (19.35%). The pitfall trap showed the percentage number of Valanga sp. (Acrididae) about 36%.